2021
DOI: 10.1186/s12936-021-03987-6
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of potential mediators of artemisinin resistance in African isolates of Plasmodium falciparum

Abstract: Background The devastating public health impact of malaria has prompted the need for effective interventions. Malaria control gained traction after the introduction of artemisinin-based combination therapy (ACT). However, the emergence of artemisinin (ART) partial resistance in Southeast Asia and emerging reports of delayed parasite sensitivity to ACT in African parasites signal a gradual trend towards treatment failure. Monitoring the prevalence of mutations associated with artemisinin resista… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 80 publications
0
20
1
Order By: Relevance
“…Therefore, the chances of getting different makers for chloroquine resistance could be higher in Malaysia. In addition, the prevalence of 80.7% in the K76T variant recorded in this study is by far higher than 12.4% in north-western Nigeria [1]. In this present study only two variants (K76T and C72S) of the PCRT gene were reported, this is contrary to the findings in previous research [43] which also reported five different variants(C72S, M74I, N75E/D K76T and A220S) of PCRT gene from India.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Therefore, the chances of getting different makers for chloroquine resistance could be higher in Malaysia. In addition, the prevalence of 80.7% in the K76T variant recorded in this study is by far higher than 12.4% in north-western Nigeria [1]. In this present study only two variants (K76T and C72S) of the PCRT gene were reported, this is contrary to the findings in previous research [43] which also reported five different variants(C72S, M74I, N75E/D K76T and A220S) of PCRT gene from India.…”
Section: Discussioncontrasting
confidence: 99%
“…Malaria is regarded as a serious global public health problem, which is partly due to it is cosmopolitan distribution and high rate of mortality traced to the disease, especially in sub-Saharan African countries that bear many consequences of the disease [1]. The disease is caused by four parasite specie in the genus Plasmodium (P. falciparum, P. vivax, P. ovale and P. malariae), recently human infections with the monkey malaria parasite, P. knowlesi, have also been reported from the forested regions of South-East [2].…”
Section: Introductionmentioning
confidence: 99%
“…As a warning, it was reported that resistance to frontline artemisinin-based drugs was spreading in the Greater Mekong Subregion of Southeast Asia. Recent studies have shown that similar artemisinin-resistant strains have appeared in Africa, which may be a dangerous signal for global malaria control ( Lubell et al, 2014 ; Slater et al, 2016 ; Stokes et al, 2021 ; L’Episcopia et al, 2021 ; Owoloye et al, 2021 ). Therefore, to prevent the resurgence of malaria in well-controlled regions and ensure the progressive decline of malaria infection in high-incidence areas, it is necessary to find more effective and safer malaria control strategies.…”
Section: Introductionmentioning
confidence: 99%
“…At the end of the last century, introduction of the artemisinin combination therapies (ACTs) provided a much needed, highly efficacious antimalarial treatment, which became the first-line treatment for uncomplicated falciparum malaria in all endemic countries [ 8 ]. The extremely rapid development of resistance to many antimalarials, and even the most recent, such as ACTs in five countries of the Greater Mekong subregion [ 9 , 10 ] and in Africa [ 11 , 12 ], justifies continued research on the factors causing this resistance. Like antibiotic resistance, antimalarial drug resistance is caused by the massive and uncontrolled use of certain molecules that could lead to a selection of resistant strains of Plasmodium over time.…”
Section: Introductionmentioning
confidence: 99%